2002
DOI: 10.1016/s0029-7844(02)02341-4
|View full text |Cite
|
Sign up to set email alerts
|

Complications after uterine artery embolization for leiomyomas

Abstract: The short-term complication rate was low in women undergoing uterine embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
1
13

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(153 citation statements)
references
References 16 publications
2
137
1
13
Order By: Relevance
“…aCL production may be induced by microbial peptides mimicking the site of fixation of anti-h 2 -glycoprotein type 1 to phospholipids. This has been demonstrated in mice 2 . A search for antiphospholipid antibodies may be useful in primary …”
Section: Sirmentioning
confidence: 63%
“…aCL production may be induced by microbial peptides mimicking the site of fixation of anti-h 2 -glycoprotein type 1 to phospholipids. This has been demonstrated in mice 2 . A search for antiphospholipid antibodies may be useful in primary …”
Section: Sirmentioning
confidence: 63%
“…In general, it is associated with a good success rate in appropriately selected patients, and severe complications such as pelvic infection and death have been reported but are rare [2]. Although infectious complications after UAE have been reported in 1% to 2% of cases [4], most of the cases had related uterine infections.…”
Section: Discussionmentioning
confidence: 99%
“…The average reduction in myoma volume is approximately 30-50%, with improvement in the symptoms and menorrhagia in more than 90% of patients. Approximately 90% of patients do not experience complications, and serious complications are reportedly rare [2]. In a recent comprehensive review including 7 randomized controlled trials (RCTs) with 793 women, UAE has been shown to be a safe, minimally invasive alternative to surgery, while patient selection and counselling should be considered due to a higher risk of requiring future surgical intervention [3].…”
Section: Introductionmentioning
confidence: 99%
“…25 Uterine artery embolization, which has shown good results, is also expensive and associated with risks. [26][27][28][29][30] Taking all of these aspects into consideration, sclerotherapy seems to be an advantageous method.…”
Section: Discussionmentioning
confidence: 99%